2019
DOI: 10.1177/0969733019871695
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ perspective on a caring relationship in clinical supervision

Abstract: Background: Nursing students spend approximately half of their time in clinical practice. It is important that clinical supervisors understand nursing students’ path of learning and can support their growth and development during the different and multifaceted learning situations offered in the clinical-practice period. Objective: Based on nursing students’ perspective and rooted in the didactics of caring science, to examine how a learning and constructive caring relationship between nursing students and supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…Previous studies focusing on students’ learning experiences in clinical practice have identified several factors that influence their learning process. These include the necessity of a close and trustful relationship with their supervisors [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. A safe relationship supports students’ professional development, protects, and assists them in times of difficulty, and guides their learning throughout clinical practice [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies focusing on students’ learning experiences in clinical practice have identified several factors that influence their learning process. These include the necessity of a close and trustful relationship with their supervisors [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. A safe relationship supports students’ professional development, protects, and assists them in times of difficulty, and guides their learning throughout clinical practice [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include the necessity of a close and trustful relationship with their supervisors [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. A safe relationship supports students’ professional development, protects, and assists them in times of difficulty, and guides their learning throughout clinical practice [ 8 ]. Honkavuo’s qualitative study of the perspective of Finnish nursing students regarding a caring relationship with their supervisor revealed that a relationship built on mutual respect and having supervisors well versed in research-based pedagogical techniques was of utmost significance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Well-functioning cooperation, where responsibility for conscious strategies for the mission of education are taken, between the universities and the healthcare organisations is crucial for interlinking caring and learning [9]. The feeling of being part of the same mission is essential if a caring relationship, built on caring ethical values and approaches, is to develop between the supervisor and the student during clinical practice [10].…”
Section: Introductionmentioning
confidence: 99%